The Cinema of Marguerite Duras Multisensoriality and Female Subjectivity - Royer, Michelle (Edinburgh University Press, 2019)
The writer Marguerite Duras was a key figure in post-war French cinema, pioneering innovations such as the disjunction of film and image, and the primacy given to voices, silence and music. Her multisensorial approach opened up new spaces for the female experience to be expressed. Although she worked with some of the best French visual technicians and musicians of her time, critiques have often neglected the visual and sonic aesthetics of her films, and their effects on spectators. Drawing on theories of embodiment and spectatorship, this book analyses the tactility and multisensoriality of Duras' films, and how they relate to her female-centred perspective.